Mechanical analysis and progressive failure prediction for fibre metal laminates using a 3D constitutive model. (September 2019) - Jin, Kai; Wang, Hao; Tao, Jie; Du, Dandan
Abstract: Because fibre metal laminates (FMLs) consist of sequentially stacked metal and fibre-reinforced polymer (FRP) laminas, obtaining an accurate description of the mechanical behaviour by a constitutive model can be difficult. In this study, a 3D constitutive model was developed to analyse the mechanical behaviours under tensile and bending conditions. Furthermore, ductile damage of metal layers, failure of FRP layers and interface delamination were predicted by 3D criteria. The influence of the fibre orientation on the mechanical properties was investigated. The stress distribution and progressive failure process of the FMLs were simulated by numerical analysis, the results of which were consistent with the experimental results.